Prevalence of heteroresistant Helicobacter pylori and treatment follow-up in patients in Ilam, Iran - Hosseini, Sanaz; Mahdian, Nahid; Gheitani, Leila; Mahmoudi, Mina; Raftari, Mohammad; Hematian, Ali; Bahmaninejad, Parvin; Badakhsh, Behzad; Ghafourian, Sobhan (German Medical Science GMS Publishing House, 2024)
Background: Special antibiotics are prescribed against . However, sometimes the bacteria are not completely eliminated, or they are recurrent. Unlike most infections, it is very difficult to eliminate a infection. Heteroresistance is defined as the phenomenon in which subpopulations of the same colony of bacteria exhibit a range of susceptibilities to a particular antibiotic. Because of heteroresistant cells, antibiotic failure and chronic infection can occur; thus, the current research aimed to investigate presence of heteroresistant cells in collected from patients reffering to clinic in Ilam, Iran. Subsequently, patients who were infected with heteroresistant were treated with antibiotics effective against heteroresistant subpopulations.Methods: In this cross-sectional descriptive study, 100 patients with clinical symptoms and suspected of being infected with were studied in private clinics in Ilam, Iran. Fiftyisolates of accompanied by patients' information were obtained from Ilam clinics. We cultured the bacteria to identify heteroresistance and to find the cause of recurrent infection in these patients. Results: Out of a total of 50 samples, 3 were heteroresistant to clarithromycin (6%). Levofloxacin was applied in cases of heteroresistant samples, and the effectiveness was determined after one month of follow-up of patients. Conclusion: Patients with heteroresistance showed sensitivity to levofloxacin. After one month of follow-up, it was found that the effectiveness of this antibiotic was good. Therefore, this antibiotic was introduced as a more effective drug in patients with heteroresistant .